342 A case series of live attenuated vaccine administration in dupilumab-treated children with atopic dermatitis. (25th January 2023) - Siegfried, Elaine C; Lee, Lara Wine; Spergel, Jonathan M; Uppal, Sumeet; Coleman, Anna; Shumel, Brad; Prescilla, Randy; Bansal, Ashish; Cyr, Sonya L
Abstract: In patients with atopic dermatitis (AD), it is unknown whether suppression of dysregulated type 2 immune cytokines, interleukin-4 and interleukin-13, with dupilumab impacts the risk of viral infections following live attenuated vaccination. Current medical consensus and regulatory labelling recommend completing age-appropriate non-live vaccinations according to immunization guidelines at least 4 weeks prior to starting dupilumab and to avoid the use of live vaccines in patients treated with dupilumab. Phase 3 dupilumab AD clinical trial protocols prohibited the administration of live attenuated vaccines within 4 weeks before the baseline visit and during treatment. For patients in the LIBERTY AD PED open-label extension (OLE; NCT02612454) who required a live attenuated vaccine, the protocol specified that the study drug be discontinued for 12 weeks prior to planned administration and could be re-initiated 4 weeks after vaccine administration. However, one patient in the 16-week LIBERTY AD PRESCHOOL (NCT03346434, part B) study received a live attenuated vaccine with a ≤ 12 weeks gap between dupilumab administration and vaccination and eight patients in the LIBERTY AD PED-OLE received a live attenuated vaccine, four patients were vaccinated with a ≤ 12 weeks gap and four patients > 12 weeks after discontinuing dupilumab. To describe the clinical course of children with moderate-to-severe AD administered a live attenuated vaccine during the LIBERTY AD PRESCHOOL or LIBERTY AD PED-OLE study. Paediatric patients with moderate-to-severe AD who had previously participated in the phase 2 open-label, multicentre, sequential study LIBERTY AD PRESCHOOL (part A; 3 or 6 mg/kg dupilumab single dose) or the randomized, double-blind placebo-controlled phase 3 study LIBERTY AD PRESCHOOL (part B; 200 mg dupilumab every 4 weeks [q4w] if baseline weight 5 to <15 kg, or 300 mg q4w if 15 to <30 kg) were subsequently enrolled into the LIBERTY AD PED-OLE study (200 mg dupilumab q4w if baseline weight 5 to <15 kg, 300 mg q4w if 15 to <30 kg, or 200 mg q2w if 30 to <60 kg). This case series includes nine patients with severe AD at the parent study baseline (Investigator's Global Assessment score = 4) and Peak Pruritus Numerical Rating Scale (range: 0–10) scores of 5.2 ( n = 1), 8 ( n = 2), 9 ( n = 4) or 10 ( n = 2), who were administered a live attenuated vaccine, with or without pause, during dupilumab treatment in the LIBERTY AD PRESCHOOL (part B; n = 1) or LIBERTY AD PED-OLE study ( n = 8). Of the nine patients in this case series, eight were male. All were first diagnosed with AD between 0 and 6 months of age and age at enrolment varied from 8 to 56 months old. Dupilumab treatment duration up to the date of vaccination with live attenuated measles, mumps, rubella (MMR) and varicella vaccines ( n = 5) or MMR vaccine only ( n = 4) ranged from 85 to 840 days. No adverse events (AEs), including serious AEs, treatment-emergent infections and infestations, or serious infections were observed in the 4-week window post-vaccination. In this limited prospective case series of children with moderate-to-severe AD who also received the live attenuated MMR vaccine, with or without live attenuated varicella vaccine, no serious adverse events were observed within 4 weeks or after 4 weeks post-vaccination. Additional research is needed to assess the safety of live attenuated vaccines in patients on dupilumab treatment and to investigate whether dupilumab treatment impacts vaccine efficacy.